Reforming borrowing regime for prudent debt management by the states - Garg, Subhash Chandra (2004)
Borrowing by different states are being used for funding non-development revenue expenditure. This article highlights the alarming proportions of debt of various states in India. This issue needs to be dealt with comprehensively with strong political will. It calls for a real fiscal tightening and adjustments besides debt control and institutional arrangements for debt authorisation. A series of policy and institutional reforms have been suggested by the author. - Reproduced.
Keywords: Debts